(untitled) - Axelrod, Alan (San Francisco, CA, 2008)
In this fascinating exploration of one of the most celebrated and innovative minds, best-selling author Alan Axelrod cuts through the myths and reverence surrounding Edison’s “genius” to show how the inventor was, in fact, an ordinary man who created extraordinary work. While many of us believe that creativity, like genius, is something that just happens by chance or destiny, Edison’s life demonstrates that creativity of the very highest order can indeed be summoned up at will, and even reduced to a reliable working method and set of principles
Keywords: Creative ability in business,Technological innovations,Khả năng sáng tạo trong kinh doanh,Đổi mới công nghệ